Different slip systems controlling crystallographic preferred orientation and intracrystalline deformation of amphibole in mylonites from the Neyriz mantle diapir, Iran. (February 2018) - Elyaszadeh, Ramin; Prior, David J.; Sarkarinejad, Khalil; Mansouri, Hadiseh
Abstract: A deformed layered gabbro and a mylonitic gabbro sample from the marginal shear zone of the Neyriz mantle diapir in Iran were analyzed using electron backscatter diffraction (EBSD). Both samples have the common amphibole crystallographic preferred orientation (CPO) in which (100) lies perpendicular to foliation and <001> parallel to lineation. Amphibole grains in the layered gabbro sample have little internal deformation, whereas in the mylonitic gabbro sample the amphibole grains are strongly distorted and contain low angle grain boundaries. There is a subtle change in CPO as a function of grain size in the mylonitic gabbro. Coarse grains (porphyroclasts) have a (100) <001> CPO oriented with the main foliation reference frame whilst fine grains have a (100) <001> CPO oriented with the C′ shear bands. Detailed analysis of porphyroclast distortions and subgrain boundary trace analysis suggests that hard slip systems, most particularly (110) <1–10> control intracrystalline deformation. Schmid factor analysis suggest that these slip systems are not involved in foliation formation but are linked kinematically to C′ shear bands. It is unlikely that the slip systems that control intracrystalline deformation are important in CPO formation. We interpret that subgrain rotation recrystallization lead to grain size reduction and the elongate recrystallized grains were rotated towards the C′ shear bands by grain boundary sliding. This rigid body rotation, possibly in combination with easy slip on (100) <001> are considered the main cause of CPO formation. Amphibole zonation patterns in the layered gabbro sample suggest that oriented growth of amphibole may have contributed to CPO. Highlights: The preserved slip systems inside the amphibole porphyroclasts are not necessarily the same ones that give rise to the CPO. Easy slip on (100) <001> and/or rigid body rotation are responsible for the amphibole CPO development. Hard slip systems control intracrystalline deformation of amphibole porphyroclasts. Hard slip systems in amphibole are not involved in foliation formation but are linked kinematically to C′ shear bands.